2020
DOI: 10.1111/jvh.13266
|View full text |Cite
|
Sign up to set email alerts
|

Temporal profile of HEV RNA concentration in blood and stool from patients with acute uncomplicated hepatitis E in a region with genotype 1 predominance

Abstract: Acute hepatitis E virus (HEV) is associated with viremia and faecal excretion of the virus. The information on duration and temporal pattern of viremia and faecal shedding in HEV infection is important, but is not available. Serial serum and stool specimens were collected from patients with acute hepatitis E (typical clinical picture, serum alanine aminotransferase levels > 5‐folds the upper limit of normal and presence of IgM anti‐HEV), beginning from within 7 days of the onset of symptoms. HEV RNA concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…While IgM antibodies decline more rapidly after an acute infection and can be detectable only for a few months after onset of symptoms, IgG antibodies can persists for at least 1 year ( 71 , 72 ). RNA on the contrary declines even more rapidly, and it is not detectable in the serum by day 20 after onset of symptoms ( 73 ). Therefore, the other two HEV IgG-reactive samples might indicate an even earlier infection as no IgM were identified in them.…”
Section: Discussionmentioning
confidence: 99%
“…While IgM antibodies decline more rapidly after an acute infection and can be detectable only for a few months after onset of symptoms, IgG antibodies can persists for at least 1 year ( 71 , 72 ). RNA on the contrary declines even more rapidly, and it is not detectable in the serum by day 20 after onset of symptoms ( 73 ). Therefore, the other two HEV IgG-reactive samples might indicate an even earlier infection as no IgM were identified in them.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of the data (n = 20) showed prevalence > 10%. The high prevalence in untreated water can be explained by the excretion of the virus via contaminated faeces or urine from infected individuals (Abravanel et al, 2015;Chandra et al, 2010;Geng et al, 2016;Goel et al, 2020;Takahashi et al, 2007). Before the onset of disease symptoms, up to 1 × 10 5 HEV genome copies per gram of faeces can be excreted for several days (Li et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this body compartment may change drastically in composition of interfering factors (digestive enzymes, pH, dilution by fluids), which makes a robust and reliable assay set-up difficult. 17 Previous studies showed a longer shedding of viral RNA in acutely as well as chronically infected HEV patients 16,18 pointing to an even increased rate of HEV RNA-positive patients at EOT in stool as compared to plasma. This further underlines the need for harmonization and specification for markers as predictors for viral relapses.…”
Section: Discussionmentioning
confidence: 99%